Citrus reticulatae pericarpium Extract Decreases the Susceptibility to HFD-Induced Glycolipid Metabolism Disorder in Mice Exposed to Azithromycin in Early Life - Lu, Hanqi; You, Yanting; Zhou, Xinghong; He, Qiuxing; Wang, Ming; Chen, Liqian; Zhou, Lin; Sun, Xiaomin; Liu, Yanyan; Jiang, Pingping; Dai, Jiaojiao; Fu, Xiuqiong; et al. (Frontiers in Immunology, 2021)
Background Studies have shown that gut microbe disorder in mice due to early-life antibiotic exposure promotes glycolipid metabolism disorder in adulthood. However, the underlying mechanism remains unclear and there is not yet an effective intervention or treatment for this process. Purpose The study investigated whether early-life azithromycin (AZT) exposure in mice could promote high-fat diet (HFD)-induced glycolipid metabolism disorder in adulthood. Moreover, the effect of citrus reticulata pericarpium (CRP) extract on glycolipid metabolism disorder via regulation of gut microbiome in mice exposed to antibodies early in life were investigated. Methods and Results Three-week-old mice were treated with AZT (50 mg/kg/day) via drinking water for two weeks and then were fed a CRP diet (1% CRP extract) for four weeks and an HFD for five weeks. The results showed that early-life AZT exposure promoted HFD-induced glycolipid metabolism disorder, increased the levels of inflammatory factors, promoted the flora metabolism product trimethylamine N-oxide (TMAO), and induced microbial disorder in adult mice. Importantly, CRP extract mitigated these effects. Conclusion Taken together, these findings suggest that early-life AZT exposure increases the susceptibility to HFD-induced glycolipid metabolism disorder in adult mice, and CRP extract can decrease this susceptibility by regulating gut microbiome.